2014
DOI: 10.3171/2014.1.jns13916
|View full text |Cite
|
Sign up to set email alerts
|

Can helmet design reduce the risk of concussion in football?

Abstract: S portS-related concussions were once believed to only result in transient symptoms and neurocognitive impairment. However, recent research has suggested potential links between repetitive concussions and neurodegenerative processes in some athletes. 6,12,13 This work has led to increased awareness and media attention on the possible long-term effects of sports-related concussions. Of all sports, football accounts for the highest incidence of concussion in the US due to the large number of athletes participati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 18 publications
1
80
0
2
Order By: Relevance
“…By understanding the injury mechanism, sports medicine professionals can make more informed decisions on improved equipment 46 and rule changes 91,92,[107][108][109] to reduce concussion incidence. 8 Biomechanical data have effectively improved player safety via protective equipment and rule changes.…”
Section: Clinical Utilitymentioning
confidence: 99%
“…By understanding the injury mechanism, sports medicine professionals can make more informed decisions on improved equipment 46 and rule changes 91,92,[107][108][109] to reduce concussion incidence. 8 Biomechanical data have effectively improved player safety via protective equipment and rule changes.…”
Section: Clinical Utilitymentioning
confidence: 99%
“…By using these models, the brain response during impact can be studied and used to determine the severity of applied load conditions and their effect on brain tissue. (Rowson et al 2014). The end result showed that one design type reduced the probability of concussion thereby validating the notion that there is connection between helmet design and mTBI (Rowson et al 2014).…”
Section: )mentioning
confidence: 99%
“…Sahler and Greenwald [1] state that preventative measures against TBI most commonly take two forms: rule changes and innovations in impact protection in the form of helmets. Rowson et al [5] examined two American football helmet designs over the course of 1.28 million impacts in games and practice, and found that helmet choice could reduce the number of concussions athletes endure. The helmet modulates energy transferred to the head, and the amount of energy transferred can differ by design.…”
Section: Introductionmentioning
confidence: 99%
“…The helmet modulates energy transferred to the head, and the amount of energy transferred can differ by design. Helmet and head injury studies tend to explore the helmets' ability to reduce the risk of TBIs and mTBIs in sport [5][6][7].…”
Section: Introductionmentioning
confidence: 99%